VGI and crisis mapping in an emergency situation. Comparison of four case studies: Haiti, Kibera, Kathmandu, Centre Italy - Saganeiti, Lucia; Amato, Federico; Murgante, Beniamino; Nolè, Gabriele (GEOmedia, 2017)
Over the last decade new voluntary mapping patterns are commonly known as VGI – Volunteered Geographic Information – that is, geo-localized information created voluntarily and consciously by web users. These are supported by platforms such as OpenStreetMap that have been shown in many emergency cases and not, a valid source of data, such detailed to be used for rescue operations. Another completely open source platform that has revolutionized the world of geographic information and how to make reports is Ushaidi that through interactive maps represents testimonies, reports, diaries, and citizen reports.